ANALYSIS OF E-WALLET USING INTENTIONS AMONG MILLENIAL GENERATION - Fitri Dewi Anggraeni; Ulfa Rabiyah; Grace T Pontoh; Mediaty Mediaty; Sri Sundari (AIBPM Publisher, 2021)
Before the development of the Corona outbreak, cash payment transactions using smartphones were already very popular in the global community but during the Covid-19 pandemic, there was an increase of 44% of Indonesians who used non-cash payments more often. This study aims to identify the perceived usefulness of e-wallet to strengthen the influence of perceived risk of COVID-19 on intention to use e-wallet. This study is a study with a quantitative approach using a survey method. The online questionnaire method was used to collect data from 172 respondents and analyzed using PLS structural equation modeling (SEM) analysis. The results of the study show that the perception of the risk of being exposed to Covid-19 has a positive effect on the intention to use the E-Wallet and the usefulness of the E-Wallet. Perception of the usefulness of e-wallet can strengthen the influence of perceived risk of covid-19 on intention to use e-wallet Keywords: E-wallet, perceived usefulness, perception of the risk